Caracterização espacial e epidemiológica da ocorrência de infecção por agentes de enfermidades transmissíveis em carnívoros selvagens e domésticos de uma área de Mata Atlântica e de floresta artificial no estado do Paraná - Galli, Gian Riccardo Ortunho [UNESP] (2015)
The investigation was carried out in farm located in an area of Atlantic and artificial forest in the municipality of Telêmaco Borba, State of Paraná, Brazil. The aims of the study were: to verify, through photografical traps, the species of wild carnivores in the region; to characterize spatially the area of life of the target species; to verify the relationships between wild and domestic carnivora in the study area; to investigate the occurrence of antibodies against Brucella, Leishmania, Leptospira, Neospora and Toxoplasma in domestic dogs and wild carnivores; to verify the knowledege of people living in the farm about the infections studied and to verify the effect of educational instruction on the knowledge of these people. Blood samples were obtained from 18 domestic dogs belonging to the farm workers, from three freeranging maned wolves (Chrysocyon brachyurus) and four free-ranging ocelots (Leopardus pardalis) captured in the area. A GPS radio transmitter housed in a collar was attached to each of the wild animals. Serological tests to Brucella abortus, B. canis, Leishmania chagasi, Leptospira spp., Neospora caninum, and Toxoplasma gondii antigens were performed. Fourteen wild carnivore species classified in twelve genera and in four families were found in the area. Only one GPS transmitter, attached to one ocelot, was found, and revealed that this animal had an area of life measuring about 25 thousand hectares. Serological tests showed antibody against B. abortus only in one maned wolf, against Leptospira in one dog, one maned wolf and three ocelots, against Neospora in two dogs, two maned wolves and two ocelots, against Toxoplasma in eigth dogs, all the three maned wolves and all the four ocelots. None of the animals had antibody titres to B. canis nor to Leishmania. The workers had initially low knowledge about the diseases, but their knowledge significantly improved after the instructions. Results of the study led to ...